The “Nixon China Shock” in the Mirror of Japanese Domestic Politics - V. V. Nelidov (Vestnik MGIMO-Universiteta, 2019)
The “Nixon China Shock” (the July 15, 1971 statement by the U.S. President R. Nixon about the recent trip of his National Security Advisor H. Kissinger to the PRC and about the President’s upcoming visit there) became one of the pivotal points in the history of Japanese foreign policy and contributed to Tokyo becoming more independent from Washington in its diplomatic course. Using the case of Japan’s reaction to this event, the article explores the characteristic features of the foreign policy making process in post-war Japan and demonstrates the considerable influence of these features on the character of Japanese foreign policy of the so-called “1955 System” period (the prolonged and continuous dominance of the conservative Liberal Democratic Party in 1955-93). The paper shows the decentralization of the foreign policy making process, expressed in the limited ability of the Prime Minister to determine foreign policy, the presence of considerable internal contradictions in the MoFA of Japan, the factionalism of the ruling party, and the high degree of dependency of the government’s policy course on the public opinion. It proves that these factors were one of the reasons for Japan’s political leadership avoiding decisive actions to normalize relations with the PRC before the “Nixon shock”, cautious that it might damage its relations with the U.S. and unable to discern the signs of upcoming U.S.-Chinese détente, and after this event, vice versa, making every effort to normalize its relations with Beijing as soon as possible, reaching this goal even before their American partners did. Given the historical importance of the “1955 System” for contemporary Japanese politics, the article’s conclusions are significant for the understanding of the logic of Japan’s domestic politics and foreign policy of the entire post-war period.Author declares the absence of conflict of interests.